2016
DOI: 10.1007/s11116-016-9717-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of out-of-home and in-home constraints on leisure activity participation in different seasons of the year

Abstract: Using multi-day, multi-period travel diaries data of 56 days (four waves of twoweek diaries) for 67 individuals in Stockholm, this study aims to examine the effects of out-of-home and in-home constraints (e.g. teleworking, studying at home, doing the laundry, cleaning and taking care of other household member[s]) on individuals' day-today leisure activity participation decisions in four different seasons. This study also aims to explore the effects of various types of working schedules (fixed, shift, partial-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Shift work may also worsen mental health and contribute to social marginalization indirectly by limiting activity participation (Harrington, 2001). A study in Stockholm suggests that shift workers engage in fewer leisure activities than other workers (Ahmad Termida et al, 2016). Beyond this study, the authors found no research examining the impacts of shift work on activity participation more broadly.…”
Section: Health and Wellbeing Impacts Of Shift Workmentioning
confidence: 68%
See 1 more Smart Citation
“…Shift work may also worsen mental health and contribute to social marginalization indirectly by limiting activity participation (Harrington, 2001). A study in Stockholm suggests that shift workers engage in fewer leisure activities than other workers (Ahmad Termida et al, 2016). Beyond this study, the authors found no research examining the impacts of shift work on activity participation more broadly.…”
Section: Health and Wellbeing Impacts Of Shift Workmentioning
confidence: 68%
“…The models include interaction terms between shift work and transportation resources, specifically transit accessibility, walkability, and vehicle access. We opted to measure all trips taken, rather than just the leisure trips which shift workers may be less likely to take part in (Ahmad Termida et al, 2016). This is because the time use survey only covers a single day for each respondent, and the probability respondents took a leisure trip on any one day is too low to make analysis of this question feasible with this data.…”
Section: Methodsmentioning
confidence: 99%
“…However, only two studies related to transport related social exclusion consider shift workers explicitly. The first draws on a 56-day travel diary of 67 individuals in Sweden, finding that shift workers engage in "less day-to-day leisure activities than other worker types" across multiple seasons (Ahmad Termida et al, 2016). The second study, an analysis of Canada's time use survey, finds these workers take just as many trips as those who work during the daytime (Palm et al, 2023).…”
Section: Social Exclusion Shift Work and Mobilitymentioning
confidence: 99%
“…This could adversely impact mental health, which is linked to social participation among some demographic groups (Takagi et al, 2013). Studies on how this affects participation in daily activities show mixed results, however (Ahmad Termida et al, 2016;Palm et al, 2023). Additionally, shift work can disrupt household dynamics, often deepening gender imbalances in domestic responsibilities (Presser, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies were conducted on in-home activity participation. Termida and Susilo ( 12 ) examined the effects of out-of-home and in-home constraints such as working-from-home, studying at home, and doing household maintenance activities on individuals’ day-to-day leisure activity participation decisions in four different seasons using dynamic ordered probit models. The study found that individuals spending longer duration in work-related activities are less likely to participate in leisure activities regardless of the season.…”
mentioning
confidence: 99%